Digital Conflict Experimentation: Strategies for Film/Video Art-Making Practise in Educational Fields - Pauhrizi, Erik Muhammad; Erika Ernawan; Dedi Warsana; Danendra Alfathadiningrat (Seni Media Rekam ISI Surakarta, 2024)
This research describes strategies in experimental film studio space, with a subjective creation process approach through the management of personal experiences of digital trauma conflicts of students of the internet user generation. The formulation of this research questions the ability of practical studio space to become a bridge of expression. This research aims to obtain the perspective of the psychological state built from the condition of trauma towards the selection of the visual language. Participatory Action Research (PAR) is conducted by reviewing and analyzing comprehensively so that all data in this study can be accounted for. The results showed that most of the students were able to recognize and manage their conflicts without being burdened by the standards of Blockbuster cinema or High Art to be empowered with creative ideas and works. In the context of self, they are able to increase their confidence as artists or academic filmmakers. This research implies that it can serve as a basis for shaping new knowledge, skills and attitudes towards the emergence of other methods of expression of film or video art creation in the future. Keywords: education; digital conflict; experimental film; video art; engaged art.